Poluição do ar dentro de barcos no litoral do estado de Paraná - Coloma, Álvaro Alfredo Parra (2019)
The burning of fossil fuels in boat engines emits solid and gaseous pollutants that impact negatively human health and the environment. One of the particulate pollutants of special interest is ultrafine particles (diameter less than 100 nm) due to their potential to reach the alveolar region and to damage the respiratory system. Black carbon (BC) particles are a fraction of UFP that, in addition to the deleterious effects on human health, contribute to global warming. In this context, for the first time in Brazil, concentrations of BC and ultrafine particle number (PN) concentrations were monitored on board ferry boats sailing along the coast of Paraná State, specifically from Paranaguá and Pontal do Sul to Ilha do Mel (an island located 4 km from the coast) in the summer of 2015. Measurements of these pollutants were also conducted in several piers and on Ilha do Mel, together with meteorological variables. The results showed a large spatial variability of BC and PN during the trips. On average, the trips from Ilha do Mel to Pontal do Sul were more polluted (mean BC 27.25 μg m-3 and PN: 2.68 x 104 cm-3) than the trip to Ilha do Mel (BC: 5.43 μg m-3 and PN: 1.05 x 104 cm-3). The sea breeze influenced the concentrations measured on board the boats, favoring the dispersion of the pollutants in some cases and in others contributing to the fumigation of these pollutants into the cabin. Tidal currents and wind interacted with the boat's shifting force, increasing the resistance to sail and, thus, raising the exhaust emissions in some cases. BC and PN measurements at fixed sites on the island were relatively low compared to mobile monitoring. On average, the lowest BC concentrations were observed at an inn (0.46 μg m-3) and at Praia Encantada beach (0.69 μg m-3), and in the case of PN the lowest mean value (0.22 x104 cm- 3) was reported at Brasília pier on the island. The average exposure for all trips was 16.34 μg m-3 for BC and 8.15 x 104 cm-3 for PN. The highest potential BC dose was observed for crew members (7.8 μg min-1), followed by adult passengers (3.55 μg min-1), elderly (3.40 μg min-1) and children (3.35 μg min-1). The PN dose reached 2.24 x 103 cm-3 min-1 for crew members and for passengers ranged from 0.96 to 1.01 x 103 cm-3 min-1. The BC exposure during the most polluted trip was 617 times higher than the exposure recorded at the hostel on Ilha do Mel. The results of this study raise concern about the occurrence of extremely high BC and PN concentrations on board ferry boats when compared with other transport modes in Brazil. More studies are needed on the water transport sector in Brazil, since passengers and crew in other regions could also be exposed to high concentrations of air pollutants.